Assessing the Risk of Antimicrobial Resistance Through Bacterial Contamination in Caregiving Environments at Jimma University Specialized Hospital - Temima Jemal; Tizita Teshome Eshetu; Dessalegn Dadi Olani; Mulunesh Deti; Zeleke Mekonnen; Gudina Terefe Tucho (Advances in Public Health)
Conclusion: As shown in the result, many isolated bacteria were resistant to the standard antibiotics commonly used to treat most diseases. Hence, admitted patients, particularly children, are at risk of infection with these antimicrobial-resistant bacteria. Due attention must be given to hygienic practices of the hospital environment and individuals to reduce the risks of contamination and transmission.